Juvenile hemochromatosis associated with heterozygosity for novel hemojuvelin mutations and with unknown cofactors - Serena Pelusi; Raffaela Rametta; Claudia Della Corte; Riccardo Congia; Paola Dongiovanni; Edoardo A. Pulixi; Silvia Fargion; Anna L. Fracanzani; Valerio Nobili; Luca Valenti (Annals of Hepatology, 2014)
Background & Aims. Juvenile hemochromatosis (JH) is a rare autosomal recessive disorder characterized by severe early-onset iron overload, caused by mutations in hemojuvelin (HJV), hepcidin (HAMP), or a combination of genes regulating iron metabolism. Here we describe two JH cases associated with simple heterozygosity for novel HJV mutations and unknown genetic factors. Case 1: A 12 year-old male from Central Italy with beta-thalassemia trait, increased aminotransferases, ferritin 9035 ng/ml and transferrin saturation 84%, massive hepatocellular siderosis and hepatic bridging fibrosis. Case 2: A 12 year-old female from Northern Italy with ferritin 467 ng/ml, transferrin saturation 87-95%, and moderate hepatic iron overload.Material and methods. Direct sequencing of hemochromatosis genes (HFE-TfR2-HJV-HAMP-FPN-1) was performed in the children and siblings.Results. In case 1, we detected heterozygosity for a novel HJV mutation (g.3659_3660insG), which was inherited together with the beta thalassemia trait from the father, who (as well as the mother) had normal iron parameters. In case 2, we detected another novel HJV mutation (g.2297delC) in heterozygosity, which was inherited from the mother, affected by mild iron deficiency. The father had normal iron stores. Both mutations are frameshifts determining premature stop codons. No other disease causing variant was detected.Conclusion. Although beta-thalassemia trait was a possible cofactor of iron overload in case 1, iron overload cannot be explained by simple heterozygosity for HJV mutations in both cases. Other genetic factors should be investigated, and further studies are needed to understand genotype-phenotype correlations in JH.